ANALYSIS OF SPECIFIC COSTS BASED ON ACTIVITIES AND ITS ROLE IN IMPLEMENTING THE DIFFERENTIATION STRATEGY (AN APPLIED STUDY IN THE DIWANIYAH TIRE FACTORY) - Donya Jasim Sahib (Scholar Express Journals, 2022)
The research aims to analyze the qualitative costs based on the activities represented by each of the costs of prevention, evaluation, internal failure and external failure in terms of improving performance efficiency and improving product and process quality in a way that can help implement the differentiation strategy efficiently and effectively in line with the requirements of the contemporary industrial environment. The research was applied in the Diwaniyah tire factory, which is one of the factories affiliated to the General Company for Rubber Industries and Tires, for the data of the year 2016. Specific costs were analyzed on the basis of activities in this factory, as the current research reached a set of conclusions, the most important of which was that the analysis of specific costs on the basis of activities to the costs of prevention, evaluation, internal failure and external failure can help the research sample factory in implementing the differentiation strategy efficiently and effectively In a manner consistent with the developments and changes that accompanied the contemporary industrial environment .
Keywords: General; environment; contemporary; industrial